Thomas Reed. Un arquitecto del siglo XIX - Saldarriaga, Alberto (Pontificia Universidad Católica del Perú, 2015)
Thomas Reed, who was born in 1817 in the Tortola Island, in the Caribbean, and passed away in Daule, Ecuador in 1878, worked as an architect and engineer in Venezuela, Colombia and Ecuador between 1843 and 1878. Most of his works were requested by the governments of these three countries, and some of them are renowned for their exceptional quality at the time. That is why his name always appears in textbooks regarding the history of architecture in the 20th century in these three countries, and in each of them he is appreciated in a diﬀerent way. Thomas Reed was an architect of his time with a solid academic background. He was also a talented engineer, well versed in structural principles and management of materials. Among his works, the most exceptional ones include the San Pablo Theater in Caracas, which was never built; the National Capitol and the former Panopticon, which is now the National Museum of Colombia in Bogotá; the Panopticon and School of Fine Arts in Quito, and the Jambelí Bridge in Ecuador. His work, inspired on the historicism of the 19th century, does not reﬂect nostalgia, but rather the way of thinking during his time. The historical time of his work is the present.

Thomas Reed, nacido en 1817 en la isla de Tórtola, en el Caribe, y fallecido en Daule, Ecuador, en 1878, trabajó como arquitecto e ingeniero en Venezuela, Colombia y Ecuador entre 1843 y 1878. La mayor parte de sus obras fueron encargadas por los gobiernos de los tres países y algunas de ellas son reconocidas por su calidad, excepcional en su momento. Por ello su nombre es referencia obligada en los textos de historia de la arquitectura del siglo XIX de los tres países, y en cada uno de ellos se lo valora en forma diferente. Thomas Reed fue un arquitecto de su tiempo, con una sólida formación académica, y un talentoso ingeniero, conocedor de los principios estructurales y del manejo de los materiales. En su obra se destacan como excepcionales el proyecto no construido del Teatro de San Pablo, en Caracas; el Capitolio Nacional y el antiguo Panóptico, hoy Museo Nacional de Colombia, en Bogotá; el Panóptico y la Escuela de Bellas Artes de Quito y el puente de Jambelí, en el Ecuador. Su empleo de los recursos del historicismo decimonónico no fue producto de la nostalgia sino propio del modo de pensar de su época. El tiempo histórico de su obra será el presente.
Keywords: Thomas Reed; Architecture; Nineteenth century; Latin America; Public architecture; Venezuela; Colombia; Ecuador; Thomas Reed; Arquitectura; Siglo XIX; América Latina; Arquitectura pública; Venezuela; Colombia; Ecuador; https://purl.org/pe-repo/ocde/ford#6.04.08